Migraine in gulf war illness and chronic fatigue syndrome: prevalence, potential mechanisms, and evaluation - Rayhan, Rakib; Ravindran, Murugan K.; Baraniuk, James N. (Frontiers in Physiology, 2013)
Objective: To assess the prevalence of headache subtypes in Gulf War Illness (GWI) and Chronic Fatigue Syndrome (CFS) compared to controls. Background: Approximately, 25% of the military personnel who served in the 1990–1991 Persian Gulf War have developed GWI. Symptoms of GWI and CFS have considerable overlap, including headache complaints. Migraines are reported in CFS. The type and prevalence of headaches in GWI have not been adequately assessed. Methods: 50 GWI, 39 CFS and 45 controls had structured headache evaluations based on the 2004 International Headache Society criteria. All subjects had history and physical examinations, fatigue and symptom related questionnaires, measurements of systemic hyperalgesia (dolorimetry), and assessments for exclusionary conditions. Results: Migraines were detected in 64% of GWI (odds ratio = 11.6 [4.1–32.5]) (mean [±95% CI]) and 82% of CFS subjects (odds ratio = 22.5 [7.8–64.8]) compared to only 13% of controls. There was a predominance of females in the CFS compared to GWI and controls. However, migraine status was independent of gender in GWI and CFS groups (x2 = 2.7; P = 0.101). Measures of fatigue, pain, and other ancillary criteria were comparable between GWI and CFS subjects with and without headache. Conclusion: The high prevalence of migraine in CFS was confirmed and extended to GWI subjects. GWI and CFS may share dysfunctional central pathophysiological pathways that contribute to migraine and subjective symptoms. The high migraine prevalence warrants the inclusion of a structured headache evaluation in GWI and CFS subjects, and treatment when present.